EFEKTIFITAS METODE COOPERATIVE LEARNING TEKNIK RECIPROCAL TEACHING DALAM PEMBELAJARAN SAKUBUN - Rohman, Yanuar Lutfi (Universitas Negeri Semarang, 2019)
This research discusses about the effectiveness of the Cooperative Learning Method Reciprocal Teaching techniques in write essays (Sakubun) learning. The purpose of this research was to find out about the write ability from UPI Japanese Education third-year students before and after using the Cooperative Learning method Reciprocal Teaching technique, to find out whether there were significant differences between the use of Cooperative Learning methods Reciprocal Teaching and drill / training methods in write essays write essays (Sakubun) learning at UPI Japanese Education third-year students and to find out the responses and impressions of UPI Japanese Education third-year students towards the use of Cooperative Learning methods in Reciprocal Teaching techniques in write essays (Sakubun) learning. In this research used the experimental method using randomized control group pre-test post-test design. To obtain data, the instruments used were in the form of written tests and questionnaires. While the samples in this research were UPI Japanese Education third-year students with a total of 50 people consisting of 25 people for the experimental class and 25 people for the control class. From the results of data analysis, it can be seen that there is a significant difference between the ability to compose students in the experimental class and the control class. In other words, the Cooperative Learning Method Reciprocal Teaching techniques is effective in increasing the student write ability. In addition, the results of the questionnaire analysis showed that the majority of students had a positive opinion on the Cooperative Learning Method Reciprocal Teaching technique which made it easier for students to write essays (Sakubun Penelitian ini membahas tentang efektifitas metode Cooperative Learning teknik Reciprocal Teaching dalam pembelajaran Sakubun. Tujuan penelitian ini untuk mengetahui bagaimana kemampuan mengarang mahasiswa tingkat III JPBJ FPBS UPI sebelum dan setelah menggunakan metode Cooperative Learning teknik Reciprocal Teaching, untuk mengetahui adakah perbedaan yang signifikan antara penggunaan metode Cooperative Learning teknik Reciprocal Teaching dengan metode drill/latihan dalam pembelajaran Sakubun pada mahasiswa tingkat III JPBJ FPBS UPI dan untuk mengetahui respon dan kesan mahasiswa tingkat III JPBJ FPBS UPI terhadap penggunaan metode Cooperative Learning teknik Reciprocal Teaching dalam pembelajaran Sakubun. Dalam penelitian ini digunakan metode eksperimen dengan menggunakan randomized control group pre-test post-test design. Untuk memperoleh data, instrumen yang digunakan berupa tes tertulis dan angket. Sedangkan sampel dalam penelitian ini adalah mahasiswa tingkat III JPBJ FPBS UPI dengan jumlah 50 orang yang terdiri dari 25 orang untuk kelas eksperimen dan 25 orang untuk kelas kontrol. Dari hasil analisis data, dapat diketahui bahwa terdapat perbedaan yang signifikan antara kemampuan mengarang mahasiswa pada kelas eksperimen dengan kelas kontrol. Dengan kata lain, metode Cooperative Learning teknik Reciprocal Teaching efektif terhadap meningkatkan kemampuan mengarang mahasiswa pada pembelajaran Sakubun. Selain itu, hasil analisis angket menunjukkan bahwa sebagian besar mahasiswa berpendapat positif terhadap metode Cooperative Learning teknik Reciprocal Teaching yaitu mempermudah mahasiswa dalam menulis karangan (Sakubun). Â© 2019 Universitas Negeri Semarang